Genetic diversity and stability analysis of sweetpotato (Ipomoea batatas Lam. L.) germplasm for leafy vegetable quality - Devarajan, Thiyagu (2012)
In Malaysia, sweetpotato has a good potential to be an important crop but currently it is not fully utilized. The leafy tops are sold in the market as vegetable, but the varieties sold are varied especially in eating quality. The objectives of this study were to evaluate the genetic diversity of leaf characters and yield components of selected twenty-two out of hundred fifty sweetpotato genotypes available in Malaysian Agriculture Research Development Institute (MARDI)’s sweetpotato germplasm collected from throughout Malaysia and other countries, subsequently to identify potential genotypes grown across different types of agro-ecology for vegetable use. In the first experiment, twenty sweetpotato genotypes were selected from MARDI’s germplasm collection and another 2 genotypes obtained from wet market, Serdang, Selangor, and were evaluated in MARDI Research Station, Serdang. The genotypes were planted with three replications on three-bed plots using randomized complete block design. The planting distance was 50 cm between bed and 25 cm within planting rows, and 20 of 30 cm shoot cuttings were used as planting materials. Results showed, morphological, yield and yield component traits were highly variable. Heritability estimates accounted for more than 80% in all traits except latex, hairiness, mature leaf size (cm) and leaf number per 10 cm shoot. In most traits a large portion of the phenotypic variance was accounted for by the genetic component. MIB12 recorded high total shoot yield (kg bed-1) followed by MIB05. Meanwhile, MIB17 had the largest leaf area (cm2), while MIB09 with the smallest. For the overall consumer acceptability score in organoleptic test, MIB05 was chosen as highly preferred genotype followed by MIB14, MIB13 and MIB15. In the second experiment, six selected genotypes from the first experiment namely, MIB05, MIB12, MIB13, MIB14, MIB15 and MIB20 were evaluated infour locations over two planting seasons. The six genotypes were selected based on shoot yield, low latex exudation, root yield and organoleptic characters. The trials were conducted at four locations, namely Serdang, Selangor (mineral soils), Telong, Kelantan (bris soils), Kundang, Selangor (tin-tailing soils) and Pontian, Johor (peat soils) with four replications using randomized complete block design in each agro-ecology. MIB05 had high total shoot yield in all agro-ecologies except in Pontian. Although MIB05 produced high shoot yield it had low or no root yields. The genotype stability analysis indicates that MIB15 was either stable or highly stable in all agroecologies in most characters using genotype-grouping techniques, nonparametric (S3i) and superiority measure (Pi) statistics. In this study, leaf area (cm2), petiole length (cm) and 30-shoots weight (kg) exhibited genotypic coeffient variation (GCV) and phenotypic coefficient variation (PCV) more than 20% and heritability more than 40% at all agro-ecologies suggesting that these characters would be very useful as a base for selection in sweetpotato breeding programs. Finally this study suggests that MIB15 is highly recommended for leafy vegetable and root production across agroecologies. Meanwhile MIB05 is recommended for shoot yield production especially for planting on bris soils.